Employee Perspectives on the Implementation of Servant Leadership in a Local Automotive Company in Indonesia: A Qualitative Case Study - Amabel Odelia Criesyhans Bawengan; M. Oktaviannur; Trenggono Pujo Sakti (Rescollacom (Research Collaborations Community), 2026)
The dynamic transformation of the business environment has encouraged organizations to adopt leadership models that are flexible and human-centered. This study examines the implementation of servant leadership from the perspective of employees in a local automotive company operating in Bandar Lampung, Indonesia. Rooted in Greenleaf’s (1970) framework, servant leadership emphasizes leaders’ commitment to serving employees through ten core characteristics, including listening, empathy, healing, awareness, persuasion, conceptualization, foresight, stewardship, commitment to employee growth, and community building. This research employs a qualitative phenomenological approach with a case study design. Data were collected through in-depth interviews, non-participant observation, and document analysis, and were analyzed using the interactive model of Miles, Huberman, and Saldaña (2020). The findings reveal that servant leadership is only partially implemented within the organization, with four characteristics conceptualization, foresight, healing, and community building being consistently practiced. Key barriers to full implementation include the predominance of indirect communication patterns, a stronger emphasis on short-term business targets over human resource development, and the absence of systematic leadership training programs. The study concludes that the application of servant leadership in non-corporate local firms requires contextual adaptation, particularly in organizations characterized by family-oriented management structures and the socio-cultural dynamics of Indonesian business practices. These findings contribute to the servant leadership literature by highlighting the contextual limitations and practical challenges of implementing human-centered leadership models in small and medium-sized enterprises in emerging economies.